The Impact of Fintech Innovation on Operational Efficiency: ‎The Mediating Role of Organizational Agility in KSA Financial Institutions - AL-Majali , Mohannad; Aldalaien, Baaeth; Allahham , Mahmoud (International Journal of Basic and Applied Sciences, 2025)
The objective of the study is to consider the impact of fintech innovation on the operating efficiency of the financial institutions in the KSA, ‎specifically, through the mediating role of organizational agility. The paper discusses the relations between fintech innovation and organizational agility and operational efficiency based on the filled questionnaires sent to both the managerial and operational teams across the various ‎types of financial institutions in KSA. The theories that lay the principles of the Resource-Based View (RBV), as fintech is being seen as a ‎technological resource, and the Dynamic Capabilities Theory (DCT), as agility is seen as a capacity that companies can apply to restructure their ‎resources, underpin the research. These results imply that operational efficiency has a considerable positive impact on fintech innovation, ‎and this effect is partially mediated by organizational agility. In that way, the richest subjects tend to implement fintech innovations to optimize the operating efficiency and performance. It is emphasized that technology innovation and business agility, as the strategic enablers of ‎sustainable effectiveness, are crucial to consider in the study. Practical Implications: KSA FIs should also invest in recent digital tools and ‎technologies and develop and sustain agile organizational architecture and agility capacity. Second, regulators are recommended to establish ‎more flexible systems to facilitate organizational agility and resilience in the financial sector in the face of continuous digital transformation‎.
Keywords: Technological Advancements; Digital Payment Systems; Financial Inclusion Tools; Operational Efficiency; Organizational Agility